Conclusions and Looking Forward - Garofalakis, Minos; Gehrke, Johannes; Rastogi, Rajeev (Data-Centric Systems and Applications book series (DCSA), 2016)
Today, data streaming is a part of the mainstream and several data steaming products are now publicly available. Data streaming algorithms are powering complex event processing, predictive analytics, and big data applications in the cloud. In this final chapter, we provide an overview of current data streaming products, and applications of data streaming to cloud computing, anomaly detection and predictive modeling. We also identify future research directions for mining and doing predictive analytics on data streams, especially in a distributed environment.